2015
DOI: 10.1128/aem.02242-15
|View full text |Cite
|
Sign up to set email alerts
|

YjeH Is a Novel Exporter of l -Methionine and Branched-Chain Amino Acids in Escherichia coli

Abstract: c Amino acid efflux transport systems have important physiological functions and play vital roles in the fermentative production of amino acids. However, no methionine exporter has yet been identified in Escherichia coli. In this study, we identified a novel amino acid exporter, YjeH, in E. coli. The yjeH overexpression strain exhibited high tolerance to the structural analogues of Lmethionine and branched-chain amino acids, decreased intracellular amino acid levels, and enhanced export rates in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…The recombinant plasmids were constructed as follows: the genes thrE and serE were amplified, digested, and ligated to the pDXW-10 plasmid that was digested with Hind III/ Bgl II. The plasmid harboring the fusion protein, SerE-EGFP (enhanced green fluorescent protein) was constructed by using the method reported in a previous study (16). To confirm the role of NCgl0581 on NCgl0580 expression, the fragment consisting of intergenic region of NCgl0581 and NCgl0580 and EGFP with or without NCgl0581 was ligated to the plasmid pDXW-11 by Clon Express MultiS One Step Cloning Kit (Vazyme, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recombinant plasmids were constructed as follows: the genes thrE and serE were amplified, digested, and ligated to the pDXW-10 plasmid that was digested with Hind III/ Bgl II. The plasmid harboring the fusion protein, SerE-EGFP (enhanced green fluorescent protein) was constructed by using the method reported in a previous study (16). To confirm the role of NCgl0581 on NCgl0580 expression, the fragment consisting of intergenic region of NCgl0581 and NCgl0580 and EGFP with or without NCgl0581 was ligated to the plasmid pDXW-11 by Clon Express MultiS One Step Cloning Kit (Vazyme, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Amino acid excretion was initiated by adding 2 mM Ser-Ser (another dipeptide). HPLC was used to determine the concentrations of amino acids (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In E. coli, Mundhada et alfound that intracellular L-serine accumulation was toxic to the engineered strain modified to produce L-serine, and that following overexpression of eamA (which encodes L-cysteine exporter in E. coli), the engineered strain exhibited increased tolerance toward L-serine with higher L-serine productivity [2]. Therefore, L-serine exporter in C. glutamicum could be a potential target for strain optimization to further improve L-serine production.It has been reported that homologs similar to the exporters in E. coli might fulfil a comparable function in C. glutamicum [17,19,20]. Accordingly, we hypothesized that the homolog to eamA (Lserine exporter in E. coli) might be involved in L-serine export in C. glutamicum.…”
mentioning
confidence: 96%
“…In brief, pre-incubated cells (in seed medium) were washed once with CGXⅡ minimal medium [41], inoculated into CGXⅡ minimal medium with 2 mM Ser-Ser (other dipeptide), and incubated for 2 h at 30 o C. Then, the cells were harvested, washed once with cold CGXⅡ minimal medium, and resuspended in CGXⅡ minimal medium. Amino acid excretion was initiated by adding 2 mM Ser-Ser (another dipeptide).HPLC was used to determine the concentrations of amino acids [19].…”
mentioning
confidence: 99%